Can partial project selection improve conservation auction performances?. Issue 2 (3rd April 2018) - Iftekhar, Md Sayed; Tisdell, John G.; Sprod, Daniel
ABSTRACT: Conservation auctions often follow an 'all or nothing' bid selection approach, which restricts the selection of the most suitable parts of a submitted project. The problem with 'lumpy' (or all-or-nothing) project selection has been identified in the literature as a major problem in conservation policy; however, the extent of the problem has been rarely quantified. Using an actual conservation tender dataset from Tasmania, the effect of the approach was estimated. This study finds that with a relatively small budget, the cost-effectiveness loss could be as high as one-quarter. To avoid such problem, a partial bid selection could be applied. The basic principle of a partial bid selection is to invite a single project from each landholder with the option for the environmental planning agency to partially select sections of the offer lands that maximise the achievement of the agency's policy objectives. A sensitivity analysis with different bid and ecological value correction factors shows that when the corrections are low, the partial selection approach could be more cost-effective than an 'all or nothing' approach. The results indicate that agencies should consider alternative project selection approaches with better targeting capabilities.